ChemInform Abstract: A Facile Microwave‐Assisted Route to Co(OH)2 and Co3O4 Nanosheet for Li‐Ion Battery. Issue 44 (14th October 2013) - Chen, Gen; Fu, Engang; Zhou, Meng; Xu, Yun; Fei, Ling; Deng, Shuguang; Chaitanya, Vimal; Wang, Yongqiang; Luo, Hongmei
Abstract Hexagonal Co(OH)2 nanosheets with average width of 2 μm and thickness of 100 nm are prepared from aqueous solutions of Co(NO3)2 and NH4OH by microwave irradiation (autoclave, 3 min).